Determination of structural phenolic compounds of Acacia dealbata pollen by HPLC/DAD - Anjos, O. (2014)
There are almost 1 380 species of Acacia found throughout the world. In Portugal the most common Acacia is Acacia dealbata Link and is an invasive species that occupy surrounding area gradually. Several studies were made in order to evaluate some potential uses for these species in order to try delaying their territorial expanding [1]. The aim of this study was to evaluate the source of flavonoids in A. dealbata pollen for use in research of new active molecules using a prior screening by HPLC/DAD. A. dealbata pollen samples were collected directly from the flower stamens and were used for the large scale extraction and isolation of flavonoids [2]. Approximately 10 mg of pollen sample was dried and extracted with 50% ethanol (1:1, v/v) assisted by ultrasonication (30 min), centrifuged at 5000 rpm during 10 min and the supernatant used for HPLC/DAD analysis in a Gilson 170 system with a Waters Spherisorb ODS2 (5 mm) (4.6 × 250 mm) column stabilized at 25 ° C by using an eluent mixture of water-acetonitrile gradient with a flow rate of 0.8 ml/min. The standard chromatograms at 260 and 340nm l [3,4] and spectral data between 220 and 400nm were collected (spectral zone of the phenolic acids and flavonoids in this study). The compounds' structures were determined by UV absorption spectroscopy according to Campos and Markham [4]. The most common flavonoids structures observed in A. dealbata pollen samples were naringenin-chalcone derivatives with different retention times. The other relevant compounds present in A. dealbata pollen were luteolin derivatives (with 6- or 8-O-substitutions), a dihydroflavonol, quercetin derivatives with 3-O-substitutions and a phenolic acid derivative and two unknown compounds (Figure 1). The two compounds not identified will be the focus of the further research. From the data collected it will be done the biological approach in order to validate some bioactivities.